Health in a post-Covid world : lessons from the crisis of western liberalism - Taylor, Sebastian (Policy Press, 2023)
What part do the values of growth and prosperity, freedom and justice, security and democracy play in social policy and human welfare? How can we judge the policies offered to us as the recipe for progress? At a time of global 'permacrisis', Sebastian Taylor applies his extensive frontline experience working with health systems and healthcare in the Global North and South to assess the concrete impact of contemporary liberal values on our welfare, development and environmental survival. Drawing on research from around the world, he uses health as an objective metric to assess how effective these policies are for individuals and society as a whole.